Advances in scar management: prevention and management of hypertrophic scars and keloids. Issue 4 (August 2016) - Del Toro, Drew; Dedhia, Raj; Tollefson, Travis T.
Abstract : Purpose of review: Abnormal scarring remains a poorly understood but functional and aesthetic consequence of surgical and traumatic wounds. The purpose of this review is to describe the current state of the science behind the prevention and management of these scars. Recent findings: A recent update in the International Clinical Recommendations on Scar Management provides a wealth of information on new and revised treatments for hypertrophic scars and keloids. Silicone-based products continue to be the premier option for prevention and initial treatment of hypertrophic and keloid scars. There is growing evidence demonstrating the efficacy of intralesional corticosteroids and 5-fluorouracil. Laser therapy remains a second-line treatment option, with low-level evidence supporting the use of pulse dye lasers and ablative fractional lasers. Summary: Although there remains no 'gold standard' for the prevention and treatment of hypertrophic scars and keloids, silicone gel products and microporous paper tape present the best conservative options. A stepwise algorithm for the treatment of hypertrophic scars or keloids based on the characteristics and responsiveness of the scar presents the best management strategy. Combination therapy (including steroid injections, 5-fluorouracil, and pulse dye laser) proves to be the strongest option for the nonsurgical management of severe hypertrophic scars and keloids.